British and American Exchange Policies I. The British Experience - Harris, S. E. (Quarterly Journal of Economics, 1934)
1. The Bank of England Operations, 1931–33, 471. — 2. The over-valued pound, 475. — 3. The theory of the British Exchange Equalization Fund, 478. — 4. The operation of the British Exchange Equalization Fund, 482. — 5. British and foreign prices and costs, 485. — 6. The export bounty, 493. — 7. Prices of imports and the balance of payments, 502.